(3GdeYLe GdJGQjNj ddZI GdYQHjI (B/s - (3GJMGO GdeLGeY GddZhjI GdYdejI GdYQHjIs; (3eLeY GddZI GdYQHjI (B((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI(B)s ((3GdTGQbI, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3efThQGJ GdbGSej,s (3eLeY GddZI GdYQHjI,s, 2021)
(3GdeYLe GdJGQjNj ddZI GdYQHjI GdPj bGe HEfLGRg GJMGO GdeLGeY GddZhjI GdYdejI GdYQHjI heLeY GddZI GdYQHjI HGdTGQbI, UOQ efg GdeLdOGJ Gd (B17 (3GdChdi, hgh GdeTQhY GddZhj GdcHjQ GdPj jQYGg UGMH GdSeh MGce GdTGQbI, hjDQN ddeQI GdChdi deaQOGJ dZI GdVGO hJMhdGJ GSJNOGegG YHQ (B17 (3bQfG eGVjI, hjNJU GdeYLe HJhVjM JGQjN GdcdeI ef MjK LPhQgG, hjHMK Yf LejY GdCdaGX GdeTJbI efgG hJbdHGJgG GdUhJjI(B. (3hjbhe HJJHY JGQjN GdcdeI GdhGMOI, hbO Je EWdGb ehbY EdcJQhfj hJWHjb Pcj ddeYLe GdJGQjNj ddZI GdYQHjI eeG jSgd Ydi GdHGMKjf eJGHYI GdJbOe aj EfLGR GdeYLe, aVdG Yf GdHMK Yf GdcdeGJ hGdfUhU(B.s
(3GdENQGL Gdafj (B: (3YGUe eMeO GdfLGQ(B.s
(3eQGLYjf GdeYLe jNJdahG eG Hjf GdCLRGA(B.s
(3GdaFI GdYeQjI (B: E.s
Keywords: (3GddZI GdYQHjIs -- (3JGQjNs -- (3eYGLes